Distribution and assessment of metals and methyl mercury in intertidal surface sediment and snail, Nerita lineata (chemnitz, 1774) in Port Klang, Selangor, Malaysia - Haris, Hazzeman (2015)
Coastal mangrove and estuarine areas are important to the environment. However,these areas are also vulnerable to the accumulation of metals in its sediment, which can be detrimental to the health of the aquatic ecosystem. Therefore, this study was conducted with the objectives of determining the distribution, enrichment and the factors affecting metals retention in sediment. Other than that, this study also aims to explore Nerita lineata potential as a biomonitor of metals in sediment and the speciation of Hg in both of these matrixes. This is because currently there are only a few studies on Hg speciation in the Malaysian environment and no study was ever conducted to determine if field collected N. lineata is suitable as a biomonitor for Co, Cr, Hg, MeHg and Mn. In order to achieve these objectives, 30 intertidal sediment samples were collected from sampling points along the coast of Port Klang, which covers the Lumut Strait, parts of the South Klang Strait and the estuaries of both the Klang River and the Langat River. The samples were then prepared according to the standard used when studying metals and mercury speciation in order to ensure data accuracy and reliability. The water and sediment samples were measured for their pH,salinity and electrical conductivity. The total dissolved solids in water and sediment particle size were also determined. Apart from that, samples of N. lineata (15 individuals per sampling station) were also collected from five predetermined sampling stations based on preliminary studies conducted. Their soft tissue was also measured for metal concentration. In general, the mean sediment metal concentration in descending order were; Fe>Mn>Zn>Cr>Pb>Ni>Cu>Co>Cd>Hg. The metal’s concentration pattern in this study differs than those previously reported in the Port Klang coastal area. This suggests that the pollution sources for this study area are also different. Accumulation of metals in the sediment was found to occur near or within the Klang and the Langat River estuaries and along the Lumut Strait. Cd, Cu, Hg, Pb and Zn were found to be enriched in the sediment as indicated by the various indices calculated. The concentration of Cr, Cu and Hg were found to exceed some of the sediment quality guidelines used around the world and the adverse effects index (AEI) also indicated that Cu and Hg at several stations could produce adverse effects to the adjacent biota. Areas within the Lumut Strait and the Klang River estuary were identified as experiencing higher ecological and toxicity risk due to the accumulation of metals. Based on investigation via the use of analytical analysis of sediment, site observation, the use of geochemical analysis and multivariate analyses, it can be concluded that the anthropogenic sources (i.e. steel related industries, shipyard, marina and jetty) from the upstream of both the Klang River and the Langat River as well as those within the study area play a crucial part in the enrichment of metals in the sediment of Port Klang. The presence of organic matter and fine grain sediment such as clay and silt were found to favour metal retention in the sediment. The soft tissue of N.lineata was found to have a mean metals concentration in the order of Fe>Zn>Mn>Ni>Cu>Pb>Co>Cr>Hg. The concentration of Cu, Mn and Pb in the soft tissue were significantly (p<0.05) positively correlated with the corresponding metals in sediment. The result of biota-sediment accumulation factor (BSAF) also indicated that Cu, Ni, Hg and MeHg were bio accumulated in N. lineata. All of this suggests that N. lineata has the potential to be used as a bioindicator for Cu, Mn, Ni, Pb, Hg and MeHg. Speciation result for Hg found that MeHg in sediment can make up from 0.06% to 94.95% of total Hg, while in N. lineata MeHg can be from 3.97% to 88.33% of total Hg. Through this study, the influence of anthropogenic activity and geographical feature on the distribution and enrichment of metals in sediment and the current state of Hg speciation in the Malaysian environment were further understood. Apart from confirming the reported ability of N. lineata as a biomonitor for Cu, Ni and Pb, this study also provides new information on its potential as a biomonitor for Hg, MeHg and Mn.